Acquaintance rape the perpetrators - Shapiro, Arnold; E. Glynn, Mary; AIMS Multimedia; Arnold Shapiro Productions ([S.l.] : Arnold Shapiro Productions, 2002)
This program presents the true nature of acquaintance rape by profiling several convicted rapists. It explores the motivations behind rape and it breaks down the rationalizations used to justify it
Executive producer, Arnold Shapiro ; producer, Mary E. Glynn ; writer, director, Susan Carney ; editor, co-producer, Shirin Basleh
Narrator : Leeza Gibbons
Keywords: Rapists -- Psychological aspects; Rapists -- Interviews; Acquaintance rape; Sex offenders